Predator densities and white‐tailed deer fawn survival. Issue 5 (8th May 2019) - Kautz, Todd M.; Belant, Jerrold L.; Beyer, Dean E.; Strickland, Bronson K.; Petroelje, Tyler R.; Sollmann, Rahel
ABSTRACT: Predation is the dominant source of mortality for white‐tailed deer ( Odocoileus virginianus ) <6 months old throughout North America. Yet, few white‐tailed deer fawn survival studies have occurred in areas with 4 predator species or have considered concurrent densities of deer and predator species. We monitored survival and cause‐specific mortality from birth to 6 months for 100 neonatal fawns during 2013–2015 in the Upper Peninsula of Michigan, USA, while simultaneously estimating population densities of deer, American black bear ( Ursus americanus ), coyote ( Canis latrans ), bobcat ( Lynx rufus ), and gray wolf ( Canis lupus ). We estimated fawn predation risk in response to sex, birth mass, and date of birth. Six‐month fawn survival pooled among years was 36%, and fawn mortality risk was not related to birth mass, date of birth, or sex. Estimated mean annual deer and predator densities were 334 fawns/100 km 2, 25.9 black bear/100 km 2, 23.8 coyotes/100 km 2, 3.8 bobcat/100 km 2, and 2.8 wolves/100 km 2 . Despite lower estimated per‐individual kill rates, coyotes and black bears were the leading sources of fawn mortality because they had greater densities relative to bobcats and wolves. Our results indicate that the presence of more predator species in a system is not entirely additive in its effect on fawn survival. © The Wildlife Society, 2019 Abstract : We estimated cause‐specific mortality of white‐tailed deer fawns in the western Upper Peninsula of Michigan, along with concurrent density of deer, coyote, American black bear, bobcat, and wolf. Results suggest that wolf and bobcat likely have the greatest per‐individual fawn kill rate, but coyote and black bear likely have the greatest population‐level effect on fawn survival as a consequence of their greater densities.